Apoptosis and changes in glucose transport early after treatment of Morris hepatoma with gemcitabine - Haberkorn, Uwe; Bellemann, Matthias E.; Brix, Gunnar; Kamencic, Huse; Traut, Ulrike; Altmann, Annette; Doll, Josef; Blatter, Johannes; Kinscherf, Ralf (European journal of nuclear medicine, 2001)
Apoptosis has been described as an energy-consuming process. This combined in vivo/in vitro study investigated the effects of the antineoplastic agent gemcitabine on tumour metabolism and on the induction of apoptosis. Dynamic positron emission tomography (PET) measurements of fluorine-18 fluorodeoxyglucose (FDG) uptake were done in rats bearing Morris hepatoma prior to and after therapy with 90 mg gemcitabine/kg b.w. Furthermore, thymidine (TdR) incorporation into the DNA of these tumours was determined. In vitro measurements of FDG and TdR uptake were performed immediately and 24 h after the end of gemcitabine treatment, and the amount of apoptotic cells was determined using the TUNEL reaction. In vivo an increase in FDG transport and phosphorylation occurred early after gemcitabine treatment, although TdR incorporation into the DNA of the tumours declined. In vitro, an enhanced glucose transport, an increase in TdR uptake in the cytoplasm and a decrease in TdR incorporation in the nucleic acid fraction early after treatment occurred. Inhibition of glucose transport caused an increase in the amount of apoptotic cells. The increase in glucose uptake and TdR metabolism early after therapy is interpreted as a stress reaction of the tumour cells, protecting the cells from apoptosis during this early period after exposure to cytotoxic drugs like gemcitabine.